Knowledge of Information Security Awareness and Practices for Home Users: Case Study in Libya - Asker, Hamida; Tamtam, Abdalmonem (European Scientific Journal, ESJ, 2023)
The abundance of information available through the internet, mobile applications, and cloud computing has made it convenient for users to access a wide range of information. However, this convenience comes at a cost, as this information is constantly at risk of being compromised by cybercriminals and hackers. While the recognition of the potential dangers of information security is increasing in developed countries, in regions like Libya in North Africa, the level of protection for this information is insufficient. The purpose of this study is to examine the various factors that may influence or affect users’ practices and awareness at home. The investigated factors are policy, behavior, training, knowledge of IT, and education. To accomplish the goals of this study, a quantitative methodology was implemented. Specifically, a survey was created to assess the correlation between key factors and security awareness and practices in the home environment. The survey attracted 220 respondents and was analyzed using Bivariate/Pearson Correlation to determine the relationship between the independent variable and the dependent variable. The results of the study showed a moderate positive correlation between policy, knowledge of IT, and education with security awareness and practice, but the behavior factor had a low correlation. These results indicate that the security awareness and practice level of employees at home is mostly at a moderate level. It is hoped that the present study provides an initial step in focusing on security training sessions among higher education employees to emphasize the importance of security training and increase knowledge of information security. It is hoped that the findings of this study will serve as a starting point for further research and a focus on providing security information for the public, which will help disseminate new knowledge on the importance of security training and increase awareness of information security.